2016
DOI: 10.1002/cbdv.201600067
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Study of Juglans regia L. Pericarps from Greece with a Chemotaxonomic Approach

Abstract: Phytochemical research of different polarity extracts from green Juglans regia L. pericarps from Greece afforded 32 compounds: four pentacyclic triterpenes (1 - 4), three sesquiterpenes (5 - 7), four tetralones (8 - 11), two naphthoquinones (12 and 13), seven phenolic acids (14 - 20), one diarylheptanoid (21), one neo-lignan (22), seven flavonoids (23 - 29), two phenylethanoids (30 and 31) and one hydrolysed tannin (32). Compounds 4 and 29 are isolated for the first time from the species, while compounds 3, 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…It has been reported that juglone was the most important phenolic compound with the highest content. This naphthoquinone was also detected in other investigations [23,24,26,121,122,136]. Recently, the 3-methoxy derivative of juglone was identified for the first time in Persian walnut husks [121].…”
Section: Chemical Constituents Of Walnut Husksupporting
confidence: 61%
See 4 more Smart Citations
“…It has been reported that juglone was the most important phenolic compound with the highest content. This naphthoquinone was also detected in other investigations [23,24,26,121,122,136]. Recently, the 3-methoxy derivative of juglone was identified for the first time in Persian walnut husks [121].…”
Section: Chemical Constituents Of Walnut Husksupporting
confidence: 61%
“…This naphthoquinone was also detected in other investigations [23,24,26,121,122,136]. Recently, the 3-methoxy derivative of juglone was identified for the first time in Persian walnut husks [121]. Meanwhile, 3-methoxy and 2-methoxy juglone have been found in the green walnut husk of J. mandshurica Maxim [144].…”
Section: Chemical Constituents Of Walnut Husksupporting
confidence: 55%
See 3 more Smart Citations